2004
DOI: 10.1093/molbev/msh110
|View full text |Cite
|
Sign up to set email alerts
|

NUMTs in Sequenced Eukaryotic Genomes

Abstract: Mitochondrial DNA sequences are frequently transferred to the nucleus giving rise to the so-called nuclear mitochondrial DNA (NUMT). Analysis of 13 eukaryotic species with sequenced mitochondrial and nuclear genomes reveals a large interspecific variation of NUMT number and size. Copy number ranges from none or few copies in Anopheles, Caenorhabditis, Plasmodium, Drosophila, and Fugu to more than 500 in human, rice, and Arabidopsis. The average size is between 62 (baker's yeast) and 647 bps (Neurospora), respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
428
2
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(446 citation statements)
references
References 23 publications
10
428
2
6
Order By: Relevance
“…Nuclear mitochondrial DNAs (NUMTs) and/or nuclear plastid DNAs (NUPTs) have been found in most eukaryotes studied so far; rates of EGT seem to vary substantially from lineage to lineage 37,38 . Although most such transfers involve small, apparently random fragments of organellar DNA that have no notable impact on the nuclear genome, entire genes can be transferred and expressed in their new environment (for example, see refs 39, 40).…”
Section: Why Do Nucleomorphs Persist?mentioning
confidence: 99%
“…Nuclear mitochondrial DNAs (NUMTs) and/or nuclear plastid DNAs (NUPTs) have been found in most eukaryotes studied so far; rates of EGT seem to vary substantially from lineage to lineage 37,38 . Although most such transfers involve small, apparently random fragments of organellar DNA that have no notable impact on the nuclear genome, entire genes can be transferred and expressed in their new environment (for example, see refs 39, 40).…”
Section: Why Do Nucleomorphs Persist?mentioning
confidence: 99%
“…The availability of whole-genome sequences of more species has enabled a more detailed study of genomic structure of NUPTs and NUMTs. Early analysis of only four species detected no correlation between the abundance of NUMTs and the size of nuclear or mitochondrial genomes (Richly and Leister, 2004a). However, recent systematic studies of dozens of species showed that the number and cumulative length of NUPTs and NUMTs correlate with both genome size and the number of organelles in cell (Hazkani-Covo et al, 2010;Smith et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear copies of mitochondrial genes (numts) have been reported in many species (Sorenson and Quinn 1998;Bensasson et al 2000;Williams and Knowlton 2001;Tourmen et al 2002;Pereira and Baker 2004;Richly and Leister 2004;Kim et al 2006;Behura 2007), including rodents (Mirol et al 2000;Triant and DeWoody 2007a, b;Gonzalez-Ittig and Gardenal 2008). These numts may be long (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These numts may be long (i.e. Kim et al 2006) and may be numerous (Richly and Leister 2004;Triant and DeWoody 2007b). Amplification of numts can be a problem in phylogenetic and systematic studies which are based on mitochondrial genes when numts are amplified in some taxa and mitochondrial copies in others, because the sequences being compared are not homologous and therefore are unlikely to reveal the evolutionary relationships of the taxa in question (Arctander 1995;Zhang and Hewitt 1996;Triant and DeWoody 2007a).…”
Section: Introductionmentioning
confidence: 99%